Modern Frontend Development with Node. js A Compendium for Modern JavaScript Web Development Within the Node.js ecosystem - Rappl, Florian (Packt Publishing, Limited, 2022)
Enhance your web development projects by fully leveraging Node.js concepts, tools, and best practices at frontend Key Features Discover the internals of Node.js, focusing on frontend web development Explore the npm frontend ecosystem, including its tooling, usage, and development processes Learn about key web development concepts such as monorepos or publishing libraries Book Description Almost a decade after the release of Node.js, the tooling used by frontend developers is fully embracing this cross-platform JavaScript runtime, which is sadly often limited to server-side web development. This is where this Node.js book comes in, showing you what this popular runtime has to offer and how you can unlock its full potential to create frontend-focused web apps. You'll begin by learning the basics and internals of Node.js, before discovering how to divide your code into modules and packages. Next, you'll get to grips with the most popular package managers and their uses and find out how to use TypeScript and other JavaScript variants with Node.js. Knowing which tool to use when is crucial, so this book helps you understand all the available state-of-the-art tools in Node.js. You'll interact with linters such as ESLint and formatters such as Prettier. As you advance, you'll become well-versed with the Swiss Army Knife for frontend developers - the bundler. You'll also explore various testing utilities, such as Jest, for code quality verification. Finally, you'll be able to publish your code in reusable packages with ease. By the end of this web development book, you'll have gained the knowledge to confidently choose the right code structure for your repositories with all that you've learned about monorepos. What you will learn Develop a frontend application with Node.js-based tools and libraries Use bundlers such as webpack or Vite to create efficient web applications Leverage test runners such as Jest to ship reliable software Organize code repositories to work in close collaboration with other developers and teams Find out how to publish npm packages to simplify code reuse Improve code quality by enabling consistent formatting using Prettier Who this book is for This book is for junior and intermediate-level frontend web developers who are looking to leverage the Node.js ecosystem for building frontend solutions. The book requires beginner-level knowledge of JavaScript, HTML, and CSS. Prior experience in using a standard shell (sh) will be beneficial.